Poly[[tetra-μ3-acetato-hexa-μ2-acetatodiaqua-μ2-oxalato-tetralanthanum(III)] dihydrate] - Yun-Xiao Liang; Qun Zhang; Shao-Min Lan; Wen-Jing Di (Acta Crystallographica Section E, 2011)
The title compound, {[La4(CH3CO2)10(C2O4)(H2O)2]·2H2O}n, exhibits a two-dimensional layered structure with the oxalate and acetate ligands acting as bridges. The asymmetric unit contains two crystallographically independent lanthanum(III) ions, half of an oxalate ligand, five acetate ligands, one coordinated water molecule and one uncoordinated water molecule. The coordination numbers of the two La ions are 9 and 10. Adjacent layers of the structure, which extend parallel to (100), are linked by O–H...O hydrogen bonds and are also held together by van der Waals interactions between the CH3 groups of the acetate anions.